2017
DOI: 10.2217/fon-2017-0494
|View full text |Cite
|
Sign up to set email alerts
|

Pacritinib and its Use in the Treatment of Patients with Myelofibrosis who have Thrombocytopenia

Abstract: The treatment landscape for myelofibrosis (MF) has reached the molecular era by targeting different pathways that are implied in this myeloproliferative neoplasm. A few years ago, the first-in-class JAK1/JAK2 inhibitor ruxolitinib, demonstrated reductions in both constitutional symptoms and splenomegaly, leading to the US FDA approval. The development or worsening of cytopenias in patients receiving ruxolitinib uncovered an unmet need that has been addressed by alternative approaches. Pacritinib, a dual JAK2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…NVP-CHZ868 was also shown to act synergistically with dexamethasone in suppressing the growth and survival of human B-ALL cells in PDX models [239]. JAK2-specific inhibitors such as pacritinib are in the final stages of clinical trials for primary and secondary MF, and display increased potency compared to currently available JAK inhibitors [233]. Gandotinib, which is in a phase 2 study for JAK2 V617F -mutated MPN treatment, showed an increased potency for the JAK2 V617F mutant [240].…”
Section: Targeting Upstream Tyrosine Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…NVP-CHZ868 was also shown to act synergistically with dexamethasone in suppressing the growth and survival of human B-ALL cells in PDX models [239]. JAK2-specific inhibitors such as pacritinib are in the final stages of clinical trials for primary and secondary MF, and display increased potency compared to currently available JAK inhibitors [233]. Gandotinib, which is in a phase 2 study for JAK2 V617F -mutated MPN treatment, showed an increased potency for the JAK2 V617F mutant [240].…”
Section: Targeting Upstream Tyrosine Kinasesmentioning
confidence: 99%
“…Ruxolitinib is the first clinically-approved JAK1/2 inhibitor for PV and MF treatment and is also in clinical trials either alone or in combination with other pharmacological agents or TKIs for HL, MM, or CML treatment (Table 2) [227][228][229][230][231][232]. Ruxolitinib and most of the JAK inhibitors that are in clinical trials are type I inhibitors, which means that they block the ATP-binding site of JAKs under the active conformation of the kinase domain [227,[233][234][235][236][237]. Type II inhibitors bind to the ATP-binding pocket of the JAK2 kinase domain in the inactive conformation, while allosteric inhibitors interact with other sites in the JAK2 protein [227].…”
Section: Targeting Upstream Tyrosine Kinasesmentioning
confidence: 99%
“…Despite these results, pacritinib is not yet approved by the FDA or the European Medicines Agency (EMA) due to toxicity concerns. Trials are currently ongoing determination of the extent of toxicity and exploring dose modifications due to concerns from early reports of intracranial haemorrhage and cardiac failure identified in the PERSIST studies [188].…”
Section: Pacritinibmentioning
confidence: 99%
“…Pacritinib is another oral multikinase inhibitor that inhibits not only JAK2 but is also targeting FLT3, IRAK1, and CSF1R. 52 In the randomized phase III trial of pacritinib vs BAT including ruxolitinib (45% of patients) for thrombocytopenic patients with myelofibrosis (PERSIST-2; NCT02055781), twice-daily treatment with pacritinib led to significant improvements in both spleen volume reduction by ≥35% and ≥50% reduction in TSS over BAT 53 In PERSIST-1 (NCT01773187) patients were randomized to either pacritinib or BAT other than ruxolitinib with higher rates of spleen responses seen in the pacritinib treated group (42 patients [19%] vs 5 patients [5%]; p=0.0003). 54 The most common adverse events with pacritinib were thrombocytopenia and anemia which seemed to be less profound than with other treatment modalities.…”
Section: Other Jak Inhibitors In Clinical Trialsmentioning
confidence: 99%